Applied ethics remembering Patrick Primeaux - Primeaux, Patrick; Schwartz, Michael; Harris, Howard (Emerald, 2012)
The late Patrick Primeaux, a past editor of this series, was an outstanding teacher of business ethics and a longtime chair of the Theology Department at St John's University in New York City. Patrick, through his teachings, research articles and books, had a profound influence on how many contemporary business ethicists both teach and think about business ethics. Some contributions in this volume are from his colleagues and reflect his influence as both a business ethics teacher and as a scholar. Others are the result of a conference held in June, 2011 at the University of Tasmania by the Australian Association for Professional & Applied Ethics. Those contributions too reflect Patrick's influence and also argue themes which Patrick would have fully endorsed.
Keywords: Business & Economics -- Business Ethics.; Philosophy -- Ethics & Moral Philosophy.; Business ethics.; Ethics & moral philosophy.; Applied ethics.; elektronické knihy; electronic books